The dynamics of returns on renewable energy companies: A state-space approach - Ripple, R.; Inchauspe, Julian; Truck, S. (Elsevier, 2015)
The renewable energy sector has accomplished remarkable growth rates over the last decade. This paper examines the dynamics of excess returns for the WilderHill New Energy Global Innovation Index, which lists firms in the renewable energy sector and is used as a global benchmark. We propose a multi-factor asset pricing model with time-varying coefficients to study the role of energy prices and stock market indices as explanatory factors. Our results suggest a strong influence of the MSCI World index and technology stocks throughout the sample period. The influence of changes in the oil price is significantly lower, although oil has become more influential from 2007 onwards. We also find evidence for underperformance of the renewable energy sector relative to the considered pricing factors after the financial crisis.